Metabolomic correlates of aerobic capacity among elderly adults. Issue 10 (30th October 2018) - Koh, Angela S.; Gao, Fei; Tan, Ru S.; Zhong, Liang; Leng, Shuang; Zhao, Xiaodan; Fridianto, Kevin T.; Ching, Jianhong; Lee, Si Y.; Keng, Bryan M. H.; Yeo, Tee Joo; Tan, Shu Y.; et al.
Abstract : Background: Aerobic capacity is a powerful predictor of cardiovascular disease and all‐cause mortality, and it declines with advancing age. Hypothesis: Since physical activity alters body metabolism, metabolism markers will likely differ between subjects with high vs low aerobic capacities. Methods: Community‐based participants without physician‐diagnosed heart disease, stroke or cancer underwent same‐day multimodal assessment of cardiovascular function (by echocardiography and magnetic resonance feature tracking of left atrium) and aerobic capacity by peak oxygen uptake (VO2 ) metrics. Associations between VO2 and cardiovascular and metabolomics profiles were studied in adjusted models including standard covariates. Results: We studied 141 participants, of whom 82 (58.2%) had low VO2, while 59 (41.8%) had high VO2 . Compared to participants with high VO2, participants with low VO2 had more adverse cardiovascular parameters, such as lower ratio of peak velocity flow in early diastole to peak velocity flow in late diastole by atrial contraction of >0.8 (76% vs 35%, adjusted odd ratio [OR] = 4.1, 95% confidence interval [CI] [1.7‐9.5], P = 0.001) and lower left atrial conduit strain (11.3 ± 4.0 vs 15.6 ± 6.1%, adjusted OR = 1.1, 95% CI [1.002‐1.3], P = 0.045). High VO2 was associated with lower accumulation of wide‐spectrum acyl‐carnitines (OR = 0.6, 95% CI [0.4‐0.9], P = 0.013), alanine (OR = 0.1, 95% CI [0.01‐0.9], P = 0.044) and glutamine /glutamate (OR = 0.1, 95% CI [0.01‐0.5], P = 0.007), compared to low VO2. Conclusion: Elderly adults with low VO2 have adverse cardiovascular and metabolic parameters compared to their counterparts with high VO2 . Combined cardiac and metabolomics phenotyping may be a promising tool to provide insights into physiological states, useful for tracking future interventions related to physical activity among community cohorts.